STUDENTS’ PERCEPTIONS TOWARD DEEPSEEK AS A SUPPORTING TOOL IN ENGLISH LANGUAGE LEARNING - Ramadhani, Oktavia; Hamid, Ade Ismail Ramadhan; Sunarti, Sunarti (English Community Journal, 2025)
In an era of rapid technological advancement, artificial intelligence (AI) has profoundly influenced various sectors, including education. This study explores university students’ perceptions of DeepSeek, an AI-powered chatbot, as a supporting tool in English language learning. Utilizing a qualitative method, the research involved interviews with eight second-semester students from the English Education Program at Universitas Muhammadiyah Kalimantan Timur. Findings reveal that students perceive DeepSeek as a beneficial tool due to its user-friendly interface, fast and concise responses, and its ability to assist in grammar correction, vocabulary development, and writing improvement. DeepSeek also fosters motivation and self-directed learning. However, limitations such as overly technical answers, daily usage restrictions, and sometimes irrelevant responses were identified. This study contributes to the ongoing discourse on AI-powered tool integration in education and highlights the potential and challenges of employing AI chatbots like DeepSeek in language learning contexts.